ANALISIS PEMBERIAN INSENTIF PEGAWAI KANTOR KECAMATAN GANEAS KABUPATEN SUMEDANG - Suherman (JRPA - Journal of Regional Public Administration, 2021)
The problem being studied in this research is the performance of structural employees. The core of the study in this research is focused on one of the factors that affect the performance of structural employees, namely the provision of incentives. Based on this, the purpose of this study is to determine whether there is an effect of providing incentives on the performance of structural employees in Ganeas District, Sumedang Regency. This study took 5 (five) respondents. Respondents in this study were structural employees who received incentives in Ganeas District, Sumedang Regency.Methods of data collection using interview and observation techniques. The interview technique was carried out in an unstructured manner using interview guidelines. The observation technique was carried out by two observers. Research data analysis is descriptive. Based on the results of the study, it was found that the provision of incentives had a positive effect on the performance of structural employees in Ganeas District, Sumedang